On poetry - Maxwell, Glyn, 1962- (Cambridge, Massachusetts : Harvard University Press, 2013)
"This is a book for anyone," Glyn Maxwell declares of On Poetry. A guide to the writing of poetry and a defense of the art, it will be especially prized by writers and readers who wish to understand why and how poetic technique matters. When Maxwell states, "With rhyme what matters is the distance between rhymes" or "the line-break is punctuation," he compresses into simple, memorable phrases a great deal of practical wisdom.
In seven chapters... the poet explores his belief that the greatest verse arises from a harmony of mind and body, and that poetic forms originate in human necessities: breath, heartbeat, footstep, posture... To illustrate his argument, he draws upon personal touchstones such as Emily Dickinson and Robert Frost. An experienced teacher, Maxwell also takes us inside the world of the creative writing class, where we learn from the experiences of four aspiring poets."--
White -- Black -- Form -- Pulse -- Chime -- Space -- Time.
Keywords: Poetry; English language -- Versification; English poetry -- History and criticism; American poetry -- History and criticism; American poetry; English language -- Versification; English poetry; Poetry; Englisch; Lyrik; USA; Criticism, interpretation, etc